Neural response to aggressive and positive interactions in violent offenders and nonviolent individuals - Taubner, Svenja; Hauschild, Sophie; Wisniewski, David; Wolter, Silke; Roth, Gerhard; Fehr, Thorsten (Brain and behavior, 2021)
Background Due to its severe negative consequences, human violence has been targeted by a vast number of studies. Yet, neurobiological mechanisms underlying violence are still widely unclear and it seems necessary to aim for high ecological validity to learn about mechanisms contributing to violence in real life. Methods The present functional magnetic resonance imaging (fMRI) study investigated the neurofunction of individuals with a history of violent offenses compared with that of controls using a laboratory paradigm requesting individuals to empathically engage in videos depicting provocative aggressive and positive social interactions from a first-person perspective. Results The contrast of aggressive vs. positive scenarios revealed midbrain activation patterns associated with caudal periaqueductal gray (PAG) in violent offenders; In controls, the rostral PAG was involved. Additionally, only in controls, this contrast revealed an involvement of the amygdaloidal complex. Moreover, in violent offenders the contrast of positive vs. aggressive situations revealed an involvement of areas in the insula, post-central gyrus and anterior cingulate cortex. Conclusions Our results support findings on the differential role of PAG subdivisions in response to threat and point to altered processing of positive social interactions in violent offenders. They further support the notion that changes in PAG recruitment might contribute to violent individuals “taking action” instead of freezing in case of threatening situations.
Gesehen am 05.12.2022